NQO1 C609T Polymorphism is Associated with Coronary Artery Disease in a Gender-Dependent Manner - Boroumand, Mohammadali; Pourgholi, Leyla; Goodarzynejad, Hamidreza; Ziaee, Shayan; Hajhosseini-Talasaz, Azita; Sotoudeh-Anvari, Maryam; Mandegary, Ali (Cardiovascular toxicology, 2017)
Findings on the association of NQO1 C609T polymorphism in the NQO1 gene and cardiovascular disease susceptibility are controversial. The objective of the current study was to examine the relationship between this polymorphism and the presence and severity of angiographically determined coronary artery disease (CAD). One-hundred and forty-five patients with newly diagnosed angiographically documented CAD (≥50 % luminal stenosis of any coronary vessel) as case group were compared to 139 controls (subjects with no luminal stenosis at coronary arteries). The presence of C609T polymorphism was analyzed using polymerase chain reaction-based restriction fragment length polymorphism. Among total population, those with combined CT/TT (T allele carrier) genotype showed a trend toward lower odds of CAD compared to those with CC (wild type) genotype, but it did not reach a statistically significant level ( p = 0.061). When data were analyzed separately for men or women, CT + TT group as compared to CC genotype was associated with decreased odds of CAD in women (adjusted OR 0.4, 95 % CI 0.2–0.9; p = 0.043), but not in men (adjusted OR 0.8, 95 % CI 0.3–1.9; p = 0.612). The C609T polymorphism within NQO1 is independently associated with CAD in women, but no association was observed in whole study population or in men.